(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Aim: The current study aimed to evaluate any potential protective effects of erythropoietin (Epo) and identify potential histological adverse changes in the stomach caused by methotrexate (MTX) therapy. Materials and Methods: There were 60 mature albino rats (about 250 g) in the study. Three equal groups of 20 rats each were created out of the animals. For 9 weeks, the animals in the first control group received intraperitoneal injections of normal saline twice a week at a dose of 0.5 mg/kg. For duration of 9 weeks, animals in Group 2 received intraperitoneal injections of MTX hydrate twice a week at a dose of 0.5 mg/kg. The animals in Group 3 were given intraperitoneal injections of MTX hydrate at a dosage of 0.5 mg/kg twice a week for 9 weeks, along with subcutaneous injections of 100 IU/kg recombinant human Epo once a week. Results and Discussion: The stomach tissue’s morphological and histological alterations were evaluated. The contents of glutathione peroxidase, superoxide dismutase, glutathione, and IL-2 and IL-6 (interleukin 6) in the serum sample were then determined. Epo demonstrated pronounced antioxidant properties and mitigated MTX’s deleterious effects on stomach histology. Conclusion: Our findings point to the need for more investigation into the potential use of Epo as a medication to shield patients from MTX’s side effects.